The Efficacy Of Interactive Video Media in Fostering EFL Students’ Listening Comprehension - Revi Nur Ridwan; Indra Yusuf Purnama; Riva Andani (Universitas Islam Negeri Palopo, 2026)
This study aimed to investigate the efficacy of interactive video media in fostering EFL students’ listening comprehension. Listening is one of the essential skills in learning English; however, many students experience difficulties in understanding spoken English due to limited vocabulary, lack of context, and low learning motivation. Therefore, the use of interactive video media was implemented to support students’ listening comprehension. This study employed a quantitative experimental research design involving two classes: an experimental class and a control class. Both classes were given a pre-test and a post-test to measure students’ listening comprehension before and after the treatment. The experimental class was taught using interactive video media, while the control class received conventional teaching methods. In addition, a questionnaire was distributed to collect students’ perceptions toward the use of interactive video media in learning listening. The results showed that students’ listening comprehension improved after the treatment. The experimental class mean score increased from 60 in the pre-test to 85 in the post-test, while the control class improved from 60 to 87. The independent samples t-test showed a significance value of 0.002, which indicates a statistically significant difference between the two groups. Furthermore, the questionnaire results revealed that most students responded positively to the use of interactive video media. In conclusion, interactive video media is an effective and engaging tool to support students’ listening comprehension in EFL learning.